Obtaining and study of physical-mechanical properties of paint materials on the basis of domestic petroleum bitumen - K. Syrmanova, K.; B. Agabekova, A.; S. Sakibayeva, A.; B. Kaldybekova, Z.; T. Botashev, Y.; B. Baizhanova, S. (International Journal of Engineering and Technology, 2019)
The article is devoted to the study of obtaining and study of physical and mechanical properties of paint materials on the basis of domestic petroleum bitumen. The expansion of the fields of application of bituminous materials is becoming more relevant due to the methods of regulation and physico-mechanical and adhesive-strength properties. The study of physical and mechanical properties of bituminous paint materials showed that water absorption changes in almost 3.5 times (from 0.03% to 0.11%), and their viability in the studied temperature range remains sufficient for the application of several layers of film from the prepared compositions. At the same time, all of them far exceed the known compositions in terms of impact strength and the magnitude of water absorption. Heat resistance of coatings does not reduce. And its value is within the permissible limits of temperatures used in technological processes.
Keywords: Oil Bitumen; Paint Materials; Viscosity; Water Absorption; Swelling; Strength; Adhesion.